Functional Characterization of a PEI-CyD-FA-Coated Adenovirus as Delivery Vector for Gene Therapy - Yao, Hong; Chen, Shih-Chi; Shen, Zan; Huang, Yun-Chao; Zhu, Xiao; Wang, Xiao-mei; Jiang, Wenqi; Wang, Zi-Feng; Bian, Xiu-Wu; Ling, Eng-Ang; Kung, Hsiang-fu; Lin, Marie C. (Current Medicinal Chemistry, 2013)
The recombinant adenovirus is evolving as a promising gene delivery vector for gene therapy due to its efficiency in transducing different genes into most types of cells. However, the host-immune response elicited by primary inoculation of an adenovirus can cause rapid clearance of the vector, impairing the efficacy of the adenovirus and hence obstructing its clinical application. We have previously synthesized a biodegradable co-polymer consisting of a low molecular weight PEI (MW 600 Da), cross-linked with β-cyclodextrin, and conjugated with folic acid (PEI-CyD-FA, named H1). Here we report that coating the adenovirus vector (Adv) with H1 (H1/rAdv) could significantly improve both the efficacy and biosafety of Adv. Enhanced transfection efficiency as well as prolonged duration of gene expression were clearly demonstrated either by intratumoral or systemic injection of a single dose of H1/rAdv in immunocompetent mice. Importantly, repeated injections of H1/rAdv did not reduce the transfection efficiency in immunocompetent mice. Furthermore, H1 transformed the surface charge of the adenovirus capsomers from negative to positive in physiological solution, suggesting that H1 coated the capsid protein of the adenovirus. This could shelter the epitopes of capsid proteins of the adenovirus, resulting in a reduced host-immune response and enhanced transfection efficiency. Taken together, these findings suggest that H1/rAdv is an effective gene delivery system superior to the adenovirus alone and that it could be considered as a preferred vehicle for gene therapy.
Keywords: H1